ANALYSIS OF THE EFFECT OF CHANGES IN MATERIAL SIZE AND STRENGTH ON STATIC HEAP LEACH STABILITY USING PFC2D SOFTWARE. - Liffa Suci, Syani
Leaching is one of the methods used to process gold ore from mining. The ore is stacked in a place called heap leach which has been prepared in such a way as to carry out the leaching process. The heap of material will then be irrigated using a sodium cyanide solution to separate the gold from other materials. There are two types of heap leach, namely static and dynamic heap leach. In dynamic heap leach, gold ore that has undergone a leaching process (spent ore) will be moved to a separate stockpile location and the heap leach will be filled with new ore for the leaching process (fresh ore). The process on static heap leach is slightly different where there is no transfer of spent ore so that the pile of fresh ore and spent ore on static heap leach will become higher and higher until it reaches a certain height. The leaching process itself can also cause fresh ore to experience a size reduction and a reduction in strength, so it is necessary to analyze the effect of reducing grain size and reducing material strength on the stability of the heap leach, especially in the static type where the slope of the heap leach is increasing in height. In this study, the effect of size reduction and strength reduction on heap leach stability was simulated using PFC2D software. The input parameters of the software are in the form of grain size distribution and material microparameters obtained from calibration results between macroparameters obtained from field data processing and laboratory testing with macroparameters obtained from UCS and UTS simulations using PFC2D. The simulation is carried out on a static heap leach slope design model which has a height of 70 meters and consists of 7 lifts. The modeling results show that the heap leach up to a height of 6 lifts does not experience fractures, while the heap leach up to a height of 7 lifts fractures approximately 8m long and the width of the fracture varies from 1cm to 13cm. In addition, from model simulations with different size distributions to simulate grain size reduction, it was found that the model with the spent ore particle size distribution (more small material) experienced a smaller displacement than the model with fresh ore particle size distribution (less small material). From this study, it can be concluded that the reduction in particle size due to the leaching process can result in a smaller heap leach displacement. However, the reduction in particle size accompanied by a reduction in the strength of the material in the static heap leach due to the leaching process can result in greater displacement and instability (experiencing cracks and the principal stress curve is in a critical area) in the static heap leach.